1997
DOI: 10.1111/j.1601-0825.1997.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Prevotella intermedia and Actinobacillus actinomycetemcomitans inhibit alkaline phosphatase activity in osteoblastic cells in vitro

Abstract: In order to study the effects of sonicated extracts from Prevotella intermedia, Actinobacillus actinomycetemcomit‐ans, Porphyromonas gingivalis, and other oral‐related bacteria, as well as Escherichia coli on bone formation, clone MC3T3‐E1 cells, which have retained osteoblastic activity, were cultured with various bacterial extracts. The addition of the sonicated extracts from Prevotella intermedia and Actinobacillus actinomycetemcomitans decreased the alkaline phosphatase activity in a dose‐dependent fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Documented effects of E. coli LPS on osteoblastic cells are mixed. No inhibitory effect of E. coli LPS were found on osteoblastic cell line MC3T3-E1 and rat calvaria cells [ 17 , 39 ]. However, Shjoi et al found an inhibitory effect on ALP activity of SaOS-2, an osteoblast-like osteosarcoma cell line [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Documented effects of E. coli LPS on osteoblastic cells are mixed. No inhibitory effect of E. coli LPS were found on osteoblastic cell line MC3T3-E1 and rat calvaria cells [ 17 , 39 ]. However, Shjoi et al found an inhibitory effect on ALP activity of SaOS-2, an osteoblast-like osteosarcoma cell line [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results do contradict the results of studies published previously. For instance, sonicated extracts of P. gingivalis had no effect on the alkaline phosphatase activity of MC3T3‐E1, a pre‐osteoblast‐like cell line (43); and P. gingivalis LPS had no effect on the cell number (as determined by DNA content) of cultures derived from the periosteum of calvarial bone (33). These contradictions may reflect different biological responses relative to the source and progenitor status of the cells analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The source and preparation of the pathogenic agent should also be considered in regard to the diversity of the published findings. Different cellular responses regarding the alkaline phosphatase activity of MC3T3‐E1 cells have been reported for sonicated extracts of P. gingivalis , P. intermedia , and Aggregatibacter (Actinobacillus) actinomycetemcomitans (43). Likewise, P. intermedia and A. actinomycetemcomitans produce different apoptopic responses on osteoblast‐like cell lines, including MG63 (45).…”
Section: Discussionmentioning
confidence: 99%
“…The capability to hinder osteogenesis seems to be a pathogenic trait restricted to a distinct group of species. Gram‐negative anaerobic rods associated with destructive periodontal disease have exhibited a collection of virulence factors that directly impair osteogenesis and induce bone loss 17‐21 . Prevotella intermedia (Pi) can inhibit osteoblast alkaline phosphatase activity and negatively affect bone formation 20 .…”
mentioning
confidence: 99%